Provenance of Aeolian Sediments in the Ordos Deserts and Its Implication for Weathering, Sedimentary Processes - Chen, Guoxiang; Dong, Zhibao; Li, Chao; Shi, Weikang; Shao, Tianjie; Nan, Weige; Yang, Junhuai (Frontiers in Earth Science, 2021)
Identifying the provenance of aeolian deposits in semi-arid zones of China is beneficial in understanding Earth’s surface processes and helping to alleviate ecological stress. In this paper, we use grain-size, geochemical elements, heavy-minerals, and quartz grain morphology data to investigate the potential source of aeolian sands from the Ordos Deserts (Mu Us Sandy Land and Hobq Desert). Sedimentological, geochemical and geomorphological results indicate that significant provenance differences exist among various parts of the Mu Us Sandy Land, i.e., aeolian sediments from the southwest region are obviously distinct from other areas in the Mu Us Sandy Land but show the same external provenance with the Hobq Desert referring to the sorting, mineralogical maturity, geochemical characteristics, heavy-minerals, and quartz grain morphology. Comparing the samples from the Ordos Deserts with felsic rocks from potential sources via a serious of geochemical methods, we conclude that: (1) Aeolian sands from other regions of the Mu Us are a mixture of binary provenance, i.e., one originated from local lacustrine sediments and underlying sandstones, and another from the Alxa Plateau (AP) carried by northwesterly Asian winter monsoon. (2) The fluvial deposits denuded from the Qilian Orogenic Belt in the Northeastern Tibetan Plateau (NTP) and carried by the Yellow River are likely the initial material source for the southwest region of the Mu Us Sandy Land and the Hobq Desert. (3) The Yellow River plays a significant and critical role in sediment transport for sand seas in arid and semi-arid areas of northern China.